2015
DOI: 10.1371/journal.pone.0135306
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Targeting the Alpha-Exosite of Botulinum Neurotoxin Serotype/A Inhibit Catalytic Activity

Abstract: The paralytic disease botulism is caused by botulinum neurotoxins (BoNT), multi-domain proteins containing a zinc endopeptidase that cleaves the cognate SNARE protein, thereby blocking acetylcholine neurotransmitter release. Antitoxins currently used to treat botulism neutralize circulating BoNT but cannot enter, bind to or neutralize BoNT that has already entered the neuron. The light chain endopeptidase domain (LC) of BoNT serotype A (BoNT/A) was targeted for generation of monoclonal antibodies (mAbs) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…We previously reported that the antibodies that most potently inhibited BoNT/A are bound at the alpha-exosite, where the α-helix of substrate SNAP-25 binds, and are remote from the substrate cleavage site [ 28 , 29 ]. In contrast, the mAbs showing the greatest inhibition of BoNT/B activity bound at the catalytic site with the degree of inhibition decreasing with distance of the epitope from the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the antibodies that most potently inhibited BoNT/A are bound at the alpha-exosite, where the α-helix of substrate SNAP-25 binds, and are remote from the substrate cleavage site [ 28 , 29 ]. In contrast, the mAbs showing the greatest inhibition of BoNT/B activity bound at the catalytic site with the degree of inhibition decreasing with distance of the epitope from the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the isolation of a single-domain camelid VHH antibody that bound the BoNT/A LC alpha exosite with a K D of 147 pM and potently inhibited SNAP25 cleavage [ 28 ]. More recently we have reported scFv and IgG mAbs that bind BoNT/A LC and inhibit SNAP25 cleavage, and like the VHH, these inhibitory mAbs bind at the alpha exosite [ 29 ]. Here, we report generation of mouse and fully human antibodies that can inhibit BoNT/B LC proteolytic activity, as well as identification of the mAb epitopes mediating this inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The BoNT/H LC-H N scFv yeast display library was constructed as described [31]. BoNT/H specific binders were isolated using three rounds of FACS sorting in which 100 nM of BoNT/H LC-H N was used for yeast incubation, followed by Alexa-647-conjugated 6F5.4 IgG (6F5.4-647) for labeling.…”
Section: Scfv Library Construction and Facs Sortingmentioning
confidence: 99%
“…In separate experiments, the BoNT/H LC-H N immunized library was also stained with 100 nM of BoNT/F5 LC-H N followed by incubation with mAb 6F5.4-647 to isolate BoNT/F5 specific mAbs. Individual colonies were picked from SD-CAA plates, cultured and scFv display induced for further characterization [31]. Libraries made from mice immunized with BoNT/F fragments [18] were sorted as described above (Table 1).…”
Section: Scfv Library Construction and Facs Sortingmentioning
confidence: 99%
“…1217 Despite promising preclinical data, none of these compounds have progressed to clinical trials, begging the need for alternative LC inhibition strategies at other sites on the enzyme; preliminary reports of α- and β-exosite inhibition have shown promise. 1821 …”
mentioning
confidence: 99%